Foreign ownership and local fans: Turkish football fans' perspective - Fişne Mücahit; Bardakçı Sait; Hasaan Syed Ali (Sciendo, 2021)
Foreign investors have been very active in football clubs in many different countries. These clubs see significant benefits from foreign investment. However, in Turkey, this practice has not yet been implemented. Furthermore, there has been no general discussion about the applicability of this system in Turkish clubs, despite almost all Turkish football clubs being in a state of financial turmoil. To fill this void, this study aims to research the views of Turkish football fans regarding the possible sale of their club to a foreign investor. A total of 1172 football fans across Turkey completed a questionnaire form for the research. The distributions of fans' views were analyzed by forming crosstabs and using the chi-square test of independence. A total of 66.8% of Turkish fans who participated in the research are against the possible sale of their club to a foreign investor, while 33.2% of the fans support this situation. Additionally, 55.5% of the fans think they have adequate information about club ownership, whereas 44.5% of them think they do not have adequate information. Also, desire for financial return, sporting success, and corporate management were found as reasons to support foreign ownership while nationalism and a sense of belonging to a club were found as reasons to oppose foreign ownership. The study indicates that fans oppose or support the idea of foreign ownership for various reasons. The study describes these factors in the context of past studies and also presents the path for future research.